Extracurricular Physical Exercise Behavior and Motivation of College Students (American Journal of Education and Technology, 2025)
The study examined the extracurricular physical exercise behavior and motivation of selected students in Xingtai Vocational College of Applied Technology. By shedding light on these effects, the study aimed to provide insights into an action plan that addressed the results. The study measured the extent of extracurricular physical exercise behavior in terms of attitude, subjective norms and perceived behavioral control. Moreover, the study also included the level of motivation in physical exercise in terms of stress control, health, sociability, competitiveness, aesthetics, and pleasure. Three hundred six students out of 1500 population size were the respondents of the study, and all the data were gathered through validated questionnaires. The findings revealed a notable high extent of extracurricular physical exercise behavior and a high level of motivation on the extracurricular physical behavior. No significant differences were observed in the extent of extracurricular physical exercise behavior and the level of motivation as grouped according to sex and course. The study emphasized the importance of implementing an action plan to address issues and improve extracurricular physical exercise. The results also highlighted the need to seek professional development opportunities and the attainment of a more profound understanding of the current industry challenges and success. The study also suggested the sufficient allocation of resources and finance.